Problems and Suggestions of Students and Teachers Regarding Rawe and Experiential Learning Programme - Singh, Shachi; Kaur, Prabhjot (International Journal of Bio-resource and Stress Management, 2018)
The present study was undertaken with the objectives to study the problems of the students and teachers and suggestions given by the students and teachers during village attachment and Experiential Learning Programme. One hundred and fifty students who had undergone RAWE during the year 2014 and 2015 were selected randomly for the study. Data were collected by following distributed questionnaire approach. Findings of the study revealed that majority of the students were having problems regarding less amount of stipend during village attachment. Difficulty in interacting with farmers regarding new technology and their participation in different activities was also perceived as a major problem by the students followed by inadequate materials for field demonstration. Lack of modern equipments and lack of transportation was evident for Experiential Learning Programme I and Experiential Learning Programme II respectively. Irregularity among students and difficulty in arrangement of transportation followed by problems regarding arranging field visits and poor documentation of records by the students were some of the major problems as perceived by the teachers. Provision of adequate and latest materials during visit to village, enhancement in stipend, provision of modern equipments for Experiential Learning Programme I and proper facilities of transportation and accommodation for Experiential Learning Programme II were some of the important suggestions given by the students to make it more effective.